104 Impacts of Phosphorus Intake on Beef Heifer Growth Performance and Reproductive Tract Scores - Hilfiker, Hailey (J Anim Sci, 2020)
This study aims to examine the effects of phosphorus intake on beef heifer growth performance and conception rates. In Northwest Arkansas, there has been an increase in phosphorus concentrations in soil where livestock manures have been repeatedly applied. Consequently, forages grown on soils high in phosphorus tend to contain high amounts of the mineral itself. This has led many to question whether it is necessary to supplement phosphorus in areas where concentrations may be higher. In this study, crossbred Angus heifers (n = 72), approximately 30 d after weaning, were stratified by body weight (average initial weight 251 ± 3.9 kg) and allocated randomly into 8 groups. Groups were assigned randomly to 1 of 2 treatments. Treatments were delivered through either 1) a free-choice-mineral mix that contained no supplemental phosphorus (CON), or 2) a free-choice-mineral mix with 4% supplemental phosphorus and identical concentrations of other supplemental minerals (4PMIN). Heifers grazed 2.42 ha mixed grass pastures with a history of livestock manure application and were supplemented with soy hulls (0.5% of body weight) daily. Data were analyzed using the mixed procedures of SAS with group as the experimental unit. Total mineral intake through d 112 did not differ (P = 0.55) between treatments. On d 112, any heifers > 273 kg body weight (n = 58) had an ultrasound evaluation of their reproductive tract. Reproductive tract score (1, infantile, to 5, corpus luteum present) did not differ (P = 0.65) due to treatment. Body weights were not different (P = 0.78) on d 112, 301 ± 5.0 kg and 299 ± 5.0 kg for CON and 4PMIN, respectively. When grazing pastures with a history of livestock manure application, levels of supplemental phosphorus in the free choice mineral did not affect heifer growth performance and reproductive tract scores.